A Supplement to the Non‐Destructive Analysis of Guan Wares From the Palace Museum (Beijing) Collection, Based on Their Body Compositions. (30th September 2014) - Li, H.; Ding, Y. Z.; Lv, C. L.; Miao, J. M.; Chen, T. M.; Tang, J. J.; Shen, Y. M.; Deng, H. Y.
Abstract : Non‐destructive EDXRF analysis has been carried out to measure the body compositions of 32 pieces of 'original' Song Guan ware and 14 pieces of Guan‐type ware of Ming and Qing imitation from the Palace Museum collection. The purpose of this study is to test the conclusions of our previous provenance study based on EDXRF analysis of glaze composition of the same samples. In agreement with the grouping derived from the glaze composition, our new data show the following. (1) Samples G1, G3, G29 and G39 are also reclassified into Ming and Qing imitations, and samples M41 and Q54 are reclassified into authentic Song Guan wares. (2) A set of seven dishes of 'original' Guan ware is reconfirmed as being made in the north of China by comparison with Ru shards from the Qingliangsi and Zhanggongxiang kilns in Ruzhou city. (3) In addition, this study suggests that three wares of 'Original' Song Guan wares (G26, G27 and G30) should be attributed to Longquan black‐body celadon. (4) The compositions of the Palace Museum Guan wares are compared with those of the shards from two Hangzhou Guan ware kiln sites. However, more work has to be done to trace the provenance of the 'authentic' Song Guan wares from the Palace Museum collection.